2017
DOI: 10.4467/20843828am.17.004.7080
|View full text |Cite
|
Sign up to set email alerts
|

On some factorial properties of subrings

Abstract: We discuss various factorial properties of subrings as well as properties involving irreducible and square-free elements, in particular ones connected with Jacobian conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For example, if X = {a, b, c}, then there is no way to define the neighborhoods of {a, b} such that they are closed to the sum. (6) The set of all strings over any alphabet with the operation of concatenation is a monoid, but is not a topological monoid. There is no natural metric or norm on the set of strings that would be consistent with concatenation.…”
Section: Proof Let Us Choose Any Open Setmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if X = {a, b, c}, then there is no way to define the neighborhoods of {a, b} such that they are closed to the sum. (6) The set of all strings over any alphabet with the operation of concatenation is a monoid, but is not a topological monoid. There is no natural metric or norm on the set of strings that would be consistent with concatenation.…”
Section: Proof Let Us Choose Any Open Setmentioning
confidence: 99%
“…Another motivation is the article [10], where the properties of square-free ideals are described. Recall that the ideal I of a ring R is called square-free if for every x ∈ R, if x 2 ∈ I, then x ∈ I. Square-free ideals are a consequence of research on the theory of square-free factorizations, the results of which can be found in the papers [4][5][6][7]9,11] (in the case of radical factorizations) and in the author's doctoral thesis, which was highly appreciated by Professor Tadeusz Krasi ński from the University of Łódź in a review, motivating the author to further work on square-free factorizations.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that in [4] the authors showed the relationship between the Jacobian hypothesis and irreducible and square-free elements in certain rings of polynomials. In this article, we will also show relationships, although not motivated by [4].…”
Section: Introductionmentioning
confidence: 99%